Elaborasi Makna Pintu sebagai Simbol dalam Arsitektur Vernakular Tionghoa, pada Bangunan Klenteng Tua di Pulau Jawa. - Kustedja, Sugiri; Sudikno, Antariksa; Salura, Purnama (Zenit, 2013)
The entrance area at a traditional Chinese temple always looks verycrowded with excessive ornaments, murals and epigraphy.  Each  point calls loudly for attention from visitors. What is  actually the philosophical ideas behind creatit? This article is based on the anthropology of traditional Chinese people’s popular cult and cosmology idea, by interpretating the symbols–while treated doors as an element of architecture-analyzed to be able to understand the meaning imply from within. A description and narration of this specific area is presented. It shows that culturally and intrinsically a traditional Chinese temple has several intense functions: documentation, didaction, continuation and preservation of Chinese culture. Keywords: hermeunatics, symbols, culture, door, vernacular architecture